(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This scientific article presents an exhaustive analysis of material selection and application for canal construction under the specific geo-climatic and hydro-technical conditions of the Andijan region in Uzbekistan. Drawing from international hydraulic engineering theory, regional construction experience, and up-to-date material science, the paper synthesizes current practices and challenges in the design, implementation, and maintenance of canal systems. Particular focus is given to the evaluation of traditional and modern construction materials—including concrete, reinforced concrete, geomembranes, clays, composites, and advanced polymer-based liners—considering their mechanical, hydraulic, and durability properties in relation to Andijan’s soil, climate, and operational demands. The review integrates experimental data, case studies, and field performance from Andijan and comparable arid to semi-arid regions, offering a critical appraisal of failure modes, economic and ecological impacts, and maintenance issues. Special attention is paid to sustainability, cost-efficiency, and technological innovation, including recommendations for improving long-term canal reliability in Uzbekistan. The article advances methodological frameworks for material selection, proposes research priorities, and outlines best practices for engineers and decision-makers engaged in water infrastructure development in Central Asia.